Social Work Students’ Perception of Education Quality, Commitment, and Competence: Comparison of Indonesia and Taiwan - Binahayati Rusyidi; Yi-Yi Chen; Yao-Chi Shih; Mary McCarthy; Yu-Hao Tseng (Social Sciences, 2023)
Competency-based education is designed to produce quality graduates and competent practitioners in social work. However, comparative studies to identify how social work education adapts to demands in practice from employers in coordination with the development of the profession across nations are rare. This study examines the influence of education quality and profession commitment on undergraduate social work students’ perceptions of their professional competence in Indonesia and Taiwan. A sample of 872 senior-year students from private and public universities was surveyed using a structured questionnaire. The analysis found that in the two countries, both education quality and professional commitment were positively associated with students’ perceptions of competence. Additionally, students’ commitment was a relatively important predictor in Indonesia but not in Taiwan. Implications for educators and profession development are discussed for societies where social work relies on the state for licensing and funding of practice.